(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This study aims to determine the relationship between stress levels and study efficiency in adolescents. The study involved students aged 13–17, and stress levels were assessed using a special questionnaire, and study efficiency was assessed using average grades and indicators of attention to study. The data obtained were statistically analyzed. The results showed that adolescents with high stress levels have relatively low study efficiency. A negative relationship was found between stress and academic performance. The results of the study indicate the importance of introducing psychological support and preventive programs aimed at reducing stress among adolescents.